Electrochemical Properties of Nanoporous Carbon Material in K+ -containing Aqueous Electrolytes - Budzulyak, I.M.; Lisovskiy, R.P.; Vashchynsky, V.M.; Rachiy, B.I.; Ivanichok, N.Ya. (Physics and Chemistry of Solid State, 2015)
The work is devoted to the study of the behavior of electrochemical systems in K+ - containing solvents. As the electrode material nanoporous carbon material was used, obtained by carbonization of plant material. Optimization of the pore size distribution was carried out with chemical-thermal method using potassium hydroxide as an activator. Parameters of supercapacitors were studied on a set AUTOLAB PGSTAT 12 using software GPES and FRA-2. Structural and morphological studies were conducted on the scanning electron microscope JSM-6700F.It is shown that the resulting materials have high values of capacity, which is realized by charge accumulation on the electrical double layer and through pseudo accumulation of ions on the surface of the material. It was established that the electrochemical capacitors based on NVM are stable over the entire range current densities, and the capacity of the material essentially depends on the optimal choice of the electrolyte.